2015
DOI: 10.1186/s12880-015-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of 18F-fluorodeoxyglucose positron emission tomography/computed tomography and 99mTc-MDP whole-body bone scanning for imaging osteolytic bone metastases

Abstract: BackgroundThe objective of this study was to evaluate the feasibility and diagnostic value of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and 99mTc-methylenediphosphonate (MDP) whole-body bone scanning (BS) for the detection of osteolytic bone metastases.MethodsThirty-four patients with pathologically confirmed malignancies and suspected osteolytic bone metastases underwent 18F-FDG PET/CT and 99mTc-MDP whole-body BS within 30 days. The sensitivity, specificity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…99m Tc-methylene diphosphonate (MDP) planar bone scan or single-photon emission computed tomography (SPECT) is widely used as noninvasive methods for detecting osseous metastases. However, these methods cannot obtain cross-sectional images of all the lesions, and they have lower resolution than other imaging techniques, such as positron emission tomography/computed tomography (PET/CT) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…99m Tc-methylene diphosphonate (MDP) planar bone scan or single-photon emission computed tomography (SPECT) is widely used as noninvasive methods for detecting osseous metastases. However, these methods cannot obtain cross-sectional images of all the lesions, and they have lower resolution than other imaging techniques, such as positron emission tomography/computed tomography (PET/CT) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…L1 and L2 vertebral body invasion are osteolytic lesions and can be identified from CT scan rather than from bone scan. 18 F-FDG PET/CT has a higher diagnostic value than whole-body 99m Tc-MDP bone scan for the detection of osteolytic bone metastases, especially in the vertebrae (12,13). PET/CT scans used in this study to detect the tumor extent only showed one case positive for bone metastasis.…”
Section: Discussionmentioning
confidence: 61%
“… 8 Bone scans are of considerable utility in detecting areas of osteoblastic activity in areas affected by trauma, infection, and arthropathy, 17 but may not detect metastatic tumors that are primarily associated with bone destruction and minimal or no osteoblastic activity. 17 18 In contrast, PET/CT has been found to show higher sensitivity than bone scans in the detection of osteolytic metastatic tumors, but lower sensitivity in detecting osteoblastic bony lesions. 19 We can therefore speculate that the bone scan did not detect mandibular metastasis, whereas the PET/CT scan showed mild hypermetabolism because our patient experienced osteolytic bone destruction in the right mandible.…”
Section: Discussionmentioning
confidence: 99%